Mannose Receptor and the Mystery of Nonhealing Leishmania major Infection - Sohrabi, Yahya; Lipoldová, Marie (Trends in parasitology, 2018)
Scientists have long puzzled over the ability of Leishmania major Seidman (LmSd) to form nonhealing cutaneous lesions in the face of a strong Th1 response. A recent study identified a population of dermal macrophages that are preferentially infected by LmSd in a mannose receptor 1-, C-type 1 (MRC1/CD206)-dependent manner.
Keywords: Leishmania major; Leishmaniasis, Cutaneous; Humans; Receptors, Cell Surface; lidé; lektiny vázající mannosu; leishmanióza kožní; Mannose-Binding Lectins; lektiny typu C; receptor mannózy; Interferon-gamma; receptory buněčného povrchu; Mannose Receptor; Lectins, C-Type; interferon gama